PENERAPAN METODE PEMECAHAN MASALAH UNTUK MENINGKATKAN KREATIVITAS DAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPA TENTANG GAYA GRAVITASI BUMI DI KELAS V SDN 9 LABUAN - Ofan Ofan (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2019)
Facts that have occurred in the learning process so far that are responsible in class V SDN 9 Labuan stillhave not provided an opportunity for students to develop creativity and critical thinking abilities of students,especially in learning Natural Sciences (IPA) about the subject of "Earth's Gravitational Force". It wasfound that almost all students did not dare to express their questions or opinions during the learningprocess. With the results of teaching experience at SDN Labuan 9 as stated above, especially the motivationand learning achievement of students is too low, so what is expected so far cannot be carried out optimally.Efforts made by the author to overcome this phenomenon, namely choosing "Problem Solving Method" inthe study of Natural Sciences (IPA) with the subject "Earth Gravitational Force", where the class isprocessed into small groups, and each small group asked to discuss the topic taught with the help of LKS(Student Worksheet) after observing the results of an experiment / demonstration conducted by each smallgroup